MENINGKATKAN PENGETAHUAN SISWA TENTANG PRESENT CONTINUOUS TENSE MELALUI LAGU DI SD KEMALA BHAYANGKARI MANADO - PARENGKUAN, DOMENIC K.S.; MARENTEK, ANDRIYANI; RANUNTU, GARRYN CH. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research’s aim is to see the students’ knowledge improvement in learning Present Continuous Tense through songs. The improvement can be seen by comparing the students' score before and after the treatment in form of teaching. The researcher used Classroom Action Research (CAR) as the research method. This research was done at the fifth grade of SD Kemala Bhayangkari Manado. The subject was all the students of the class which consists of 22 students. Steps that the researcher took in collecting the data were: Pre-test, Treatment, and Post-test. The data were analyzed in quantitative ways which obtained from the students’ pre-test and post-test score. The research finding indicated that learning with songs improved the students’ knowledge about Present Continuous Tense. The improvement was shown from the increased score of the students in Post-test after the treatment. The students’ main score on the pre-test was 49.99, and the students’ main score in the post-test was 83.5. The average score of post-test is higher than pre-test. In other words, There was an improvement of 67.33%. Based on the findings, it can be concluded that learning present continuous using songs is effective. Keywords: CAR, Songs, Present Continuous Tense, Quantitative Research, Elementary School.